2012
DOI: 10.4081/ejh.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Application of alternative fixatives to formalin in diagnostic pathology

Abstract: Fixation is a critical step in the preparation of tissues for histopathology. The aim of this study was to investigate the effects of different fixatives vs formalin on proteins and DNA, and to evaluate alternative fixation for morphological diagnosis and nucleic acid preservation for molecular methods. Forty tissues were fixed for 24 h with six different fixatives: the gold standard fixative formalin, the historical fixatives Bouin and Hollande, and the alternative fixatives Greenfix, UPM and CyMol. Tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 17 publications
3
20
1
1
Order By: Relevance
“…The MKI67 and p53 labeling indices were established as the percentage of tumoral cells with positive nuclei. For the grading, a mitotic count O2 was considered positive and the threshold for MKI67 index positivity set at O1% rather than O3%, taking into account the use of Bouin-Hollande fixative solution that results in a lower sensitivity for the MKI67 antibodies than formalin (16,17). For p53, detection was considered as positive if there were more than ten strongly positive nuclei per 10 HPF (HPF of 0.30 mm 2 ; 400!…”
Section: Markers Of Proliferationmentioning
confidence: 99%
“…The MKI67 and p53 labeling indices were established as the percentage of tumoral cells with positive nuclei. For the grading, a mitotic count O2 was considered positive and the threshold for MKI67 index positivity set at O1% rather than O3%, taking into account the use of Bouin-Hollande fixative solution that results in a lower sensitivity for the MKI67 antibodies than formalin (16,17). For p53, detection was considered as positive if there were more than ten strongly positive nuclei per 10 HPF (HPF of 0.30 mm 2 ; 400!…”
Section: Markers Of Proliferationmentioning
confidence: 99%
“…However, Bouin's solution has very low pH, contains picric acid, which can be explosive, and is sensitive to friction and shock when dry. Further, a recent study showed that fixation in Bouin's solution did not provide IHC results comparable to those obtained with formalin . Fixatives containing mercuric chloride like Zenker's fixative and B5 were also widely shown to be suitable for IHC studies , but are toxic; their disposal as hazardous waste is costly, and these reagents are not allowed in many countries at this time.…”
Section: Special Considerations For Pre‐analytical Phasementioning
confidence: 99%
“…Some of the frequently encountered issues include the techniques having a high cost, being labor‐intensive, and yielding less than adequate cellular material for diagnosis or ancillary testing. Some techniques use fixatives other than formalin, which may interfere with immunohistochemical (IHC) studies . The automated method currently available is expensive and time‐consuming, produces limited numbers of slides, and uses alcohol as the fixative.…”
Section: Introductionmentioning
confidence: 99%
“…Some techniques use fixatives other than formalin, which may interfere with immunohistochemical (IHC) studies. 8 The automated method currently available is expensive and time-consuming, produces limited numbers of slides, and uses alcohol as the fixative. To resolve these issues, we developed a formalin-fixed, paraffin-embedded cytology cell block technique, AFFECT, to make cell blocks.…”
Section: Introductionmentioning
confidence: 99%